KAJIAN TEKNIK, METODE, IDEOLOGI PENERJEMAHAN PADA KOMIK BABY BLUES SIAGA SATU ANAK PERTAMA KARYA RICK KIRKMAN DAN JERRY SCOTT DAN PENGARUHNYA TERHADAP KUALITAS TERJEMAHAN - Hosnol Wafa`; Indra Tjahyadi (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. The objectives of this study are Analysis of techniques, methods, and ideologiesused by translator on translation form and function directive illocutionary of speech act and to assess the quality of translation form and function directive illocutionary of speech act used in bilingual comic Baby Blues siaga satu anak pertama from accuracy, acceptability, and readability of translation aspects. This research was a descriptive, qualitative, and embedded research of translation. The finding of this study shows; first, 273 data of directive illocutionary utterances applied 11 function, such as commanding, asking, asserting, inviting, requesting, ordering, advicing, suggesting, urgeing, rejecting, forbiding, recommending, reminding, and convinceing. Second, 273 data of directive illocutionary utterances analyzed, translation technique identified 248 data oriented to source language and 163 data oriented to target language. Thirth, concerning with translation quality of directive illocutionary speech act utterance in comic Baby Blues siaga satu anak pertama can be concluded that the translation is accurate. In this case is showed from 255 data constitute the translation accurate, 17 data less accurate, and 1 data not accurate, 254 data acceptability, 18 data less acceptability, and 1 data not acceptability, then 161 data high readability, 97 data medium readability, and 15 data low readability translation. Keywords: Directiveillocutionary, Techniques, Methods, Ideologies, Translation quality